The issue of relationship between emotions, emotionality and activity - Pacevičius, J. (Psichologija, 1995)
An analysis of experimental work on the problem of relationship between emotions and activity is presented here. Situative and stable (typical) aspects of the analysis emotional phenornena, manifesting itself in activity, is distinguished. The contradictive character of experimental data conceming the problem of emotion anei activity rclation is stressed. The necessity of paying auention to stable emotional peculiarities in investigating tbe influence of situative emotions on activity is shown. The necessity for investigations not only a resultive side of activity and not only a quantitative parameters (intensity) of emotionality is stressed. The prospect for deeper analysis is open including into investigations processive indences of activity and qualitative (sign, modality) parameters of emotions